Weavers, scribes, and kings: a new history of the Ancient Near East - Podany, Amanda H. ca. 20./21. Jh. (Oxford University Press, 2022)
A sweeping history of the ancient Near East from 3500 to 323 BCE,Weavers, Scribes, and Kings is built around the life stories of many ancient men and women. Their habits of daily life, beliefs, triumphs, and crises, and the changes that they faced over time are explored through their own written words and the buildings, cities, and empires in which they lived.